Training-fuel coupling (TFC): A molecular sports nutrition framework for energy availability, chrono-nutrition, and performance optimization - Stoian, M.; Manescu, D. C. (Nutrients, 2026)
In sports nutrition, performance adaptation emerges from the coordinated molecular interaction between physical training and nutrient availability. This narrative review with conceptual synthesis advances Training-Fuel Coupling (TFC) as a systems physiology framework that conceptualizes nutrient availability, timing, and recovery feeding as molecular control variables proposed to govern exercise-induced adaptation. Integrating evidence from exercise metabolism and nutritional science, the model conceptualizes how substrate availability may modulate the dynamic crosstalk between AMP-activated protein kinase (AMPK) and mechanistic target of rapamycin (mTOR), shaping metabolic flexibility, anabolic recovery, and long-term performance optimization. Low-energy and low-glycogen contexts preferentially activate AMPK-dependent pathways supporting mitochondrial remodeling and oxidative efficiency, whereas nutrient-replete states facilitate mTOR-mediated protein synthesis and structural restoration. When strategically alternated through chrono-nutrition and nutritional periodization, these energetic states are hypothesized to generate oscillatory signaling patterns that enhance adaptive efficiency while limiting chronic metabolic strain. From a sports nutrition perspective, TFC provides a mechanistic rationale for energy availability management, recovery nutrition, and the prevention of maladaptive states such as Relative Energy Deficiency in Sport (RED-S). By reframing nutrients as regulatory signals rather than passive fuel, this framework integrates molecular nutrition with performance physiology, offering a unifying, systems-level and hypothesis-generating perspective on training-nutrition interactions that delineates testable pathways for future empirical investigation.